2015
DOI: 10.1007/s10803-015-2649-5
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Disseminating Information on Biomedical Research on Autism to Hispanic Parents

Abstract: Low income Hispanic families experience multiple barriers to accessing evidence-based information on Autism Spectrum Disorders (ASD). This study utilized a mixed-strategy intervention to create access to information in published bio-medical research articles on ASD by distilling the content into parent-friendly English- and Spanish-language ASD Science Briefs and presenting them to participants using two socially-oriented dissemination methods. There was a main effect for short-term knowledge gains associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Universal screening, which has recently been reported to help reduce minority children’s underidentification for both gifted education services (Card & Giuliano, 2015) and pediatric care (Payne & Puumala, 2013), may help counteract underidentification resulting from the system’s current reliance on parent- and teacher-based referral as well as help counter an observed reluctance by schools to appropriately identify and provide services to minority children, including those with independently identified disabilities (Gillborn et al, 2016). Providing minority parents with accessible scientific information about specific disability conditions may also be helpful (Lajonchere et al, 2016). These and additional efforts by researchers, policymakers, and practitioners may be necessary to successfully address racial and ethnic disparities in disability identification in U.S. schools, which are longstanding as well as widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Universal screening, which has recently been reported to help reduce minority children’s underidentification for both gifted education services (Card & Giuliano, 2015) and pediatric care (Payne & Puumala, 2013), may help counteract underidentification resulting from the system’s current reliance on parent- and teacher-based referral as well as help counter an observed reluctance by schools to appropriately identify and provide services to minority children, including those with independently identified disabilities (Gillborn et al, 2016). Providing minority parents with accessible scientific information about specific disability conditions may also be helpful (Lajonchere et al, 2016). These and additional efforts by researchers, policymakers, and practitioners may be necessary to successfully address racial and ethnic disparities in disability identification in U.S. schools, which are longstanding as well as widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of Latinos’ research dissemination preferences have suggested that while favored communication methods (i.e., over the phone, in person, through the mail using printed materials, via text message) are setting and context dependent, simple low-technology approaches like typed letters are widely accepted. 14,15 Despite the interest in personal results we saw in the focus groups, the decision was made to report only aggregate findings due to the substantial logistical and ethical issues involved in returning personalized research results. 16,17 Additionally, most PUEDO informed consent forms did not allow for return of individual results.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à subcategoria das "fontes informais", verificou-se que os pais obtinham informações de outros pais de crianças com TEA e de amigos em condições semelhantes (11,20,22,24,31,35,55). Famílias compartilhavam informações com o cônjuge e outros membros, tais como irmãos, tios, primos e os avós da criança (12,30,34,38), outros membros da rede pessoal, como vizinhos, amigos (32,33,37,38) e grupos de apoio ou associações (11,(28)(29)(30)52). Os avós têm um papel importante no compartilhamento de informações e no apoio aos pais de crianças com TEA (48).…”
Section: Fontes De Suporte Informacional Acessadas Pelas Famíliasunclassified